Żywa śmierć, martwe życie: Lacan, Badiou i utracony skarb liberalizmu - Masłoń, Sławomir (Er(r)go. Teoria - Literatura - Kultura, 2008)
Sławomir Masłoń Living Death, Dead Life. Lacan, Badiou and the Lost Treasure of Liberalism Using as a springboard an essay by Agata Bielik-Robson in which she criticizes the recent revival of the connection between Marxism and Lacanian psychoanalysis as the reincarnation of deadly rhetoric (fanatic and fantasmatic) and opposes it to the origins of liberalist discourse as the modern language of pure vitalist energy, the text tries to show that such an ecstatic interpretation of liberalism is precisely the fantasmatic counterpart of the drab and life-denying “the end of grand narratives” ruling ideology. It also attempts to show that the opposition between the supposed ideological adulation of death (Lacan) and life (liberalism) is not only based on erroneous understanding of crucial Lacanian concepts, but also on a questionable conceptualization of the notion of life itself.